Ferroptosis: A Trigger of Proinflammatory State Progression to Immunogenicity in Necroinflammatory Disease - Li, Jing-yan; Yao, Yong-ming; Tian, Ying-ping (Frontiers in Immunology, 2021)
Until recently, necrosis is generally regarded as traumatic cell death due to mechanical shear stress or other physicochemical factors, while apoptosis is commonly thought to be programmed cell death, which is silent to immunological response. Actually, multiple modalities of cell death are programmed to maintain systematic immunity. Programmed necrosis, such as necrosis, pyroptosis, and ferroptosis, are inherently more immunogenic than apoptosis. Programmed necrosis leads to the release of inflammatory cytokines, defined as danger-associated molecular patterns (DAMPs), resulting in a necroinflammatory response, which can drive the proinflammatory state under certain biological circumstances. Ferroptosis as a newly discovered non-apoptotic form of cell death, is characterized by excessive lipid peroxidation and overload iron, which occurs in cancer, neurodegeneration, immune and inflammatory diseases, as well as ischemia/reperfusion (I/R) injury. It is triggered by a surplus of reactive oxygen species (ROS) induced in an imbalanced redox reaction due to the decrease in glutathione synthesis and inaction of enzyme glutathione peroxidase 4 (GPX4). Ferroptosis is considered as a potential therapeutic and molecular target for the treatment of necroinflammatory disease, and further investigation into the underlying pathophysiological characteristics and molecular mechanisms implicated may lay the foundations for an interventional therapeutic strategy. This review aims to demonstrate the key roles of ferroptosis in the development of necroinflammatory diseases, the major regulatory mechanisms involved, and its potential as a therapeutic target.